SISTEM PENDUKUNG KEPUTUSAN PEMBERIAN BANTUAN MESIN KETINTING BAGI NELAYAN DESA BAJO MENGGUNAKAN METODE ADDITIVE RATIO ASSESSMENT - Azwar; Hamria; Anas (CV. LAJAGOE PUSTAKA, 2023)
This study aims to design a decision support system to provide ketinting machine assistance for fishing communities in Bajo village. As well as selecting to provide ketinting machine assistance. The method used in this study is the Additive Ratio Assessment (ARAS) method. The ARAS method is used in this study because it can rank by comparing one alternative with another to provide more precise and accurate results. The results obtained in this study are the results of the purchase ranking of recipients of the highest ketinting machine assistance received in calculating the ARAS method so that the value of the order can provide information about recipients of ketinting machine assistance.